Determinants of Group Dynamics among Rice Farmers in Ogun State, Nigeria - Dada, O. M.; Idowu, A. O.; Aderinto, A.; Oyebanjo, O.; Ologbon, O. A.C. (NIU Journal of Social Sciences; Vol 7 No 1 (2021): KIU Journal of Social Sciences, Vol. 7 No. 1, March 2021, 2021)
Low productivity of rice occasioned by limited access to agricultural inputs is a major setback in achieving food security. Adoption of farmersâ€™ group has been the model engaged by development agencies to facilitate access to agricultural inputs among Nigerian rice farmers. This study investigated the determinants of group dynamics as well as benefits derived among rice farmers in Ogun State. A structured interview schedule was used to collect information from 161 rice farmers through a three-stage sampling procedure. Data were analysed using descriptive statistics, ranking, Chi-square, Pearson Product Moment Correlations (PPMC), and Principal Component Analysis (PCA) at pâ‰¤0.05. Finding revealed that Group Dynamic Index (GDI) was 0.64. Group members (60.9%) had access to agricultural inputs. Sale of produce ranked 1st among benefits derived by members followed by access to information and capacity building. Age (Ï‡ 2 = 20.32), education (Ï‡ 2 = 12.59), farming experience (r= - 0.04), household size (r= 0.03) and access to agricultural inputs (r=0.91) had significant relationship with group dynamics. Outcome of group dynamic was reduced by corruption among leaders (0.909), conflict among members (0.905), lack of cooperation (0.900) and poor management (0.890).Therefore, the study recommended proper monitoring by members and authorities for group activities. There is a need to build capacities of group members and officials through effective training in order to promote their understanding of group dynamics and benefits. Keywords: Group dynamics, access to inputs, rice farmers, leadership, benefits